Gestão por resultados: disseminação e engajamento dos servidores para implementação do planejamento estratégico municipal: propostas à prefeitura municipal de Osasco - Cerqueira, Bruna (2015)
This study was conducted in order to identify the main challenges of dissemination and body employee engagement and seek answers to propositional form from a municipal strategic planning and, through this, excise the case in Osasco, through its Secretariat of Planning and Management (SEPLAG), sought to consolidate the full development of its plan at the local level. There were face to face interviews with representatives of SEPLAG, the Communications Secretariat (SECOM) and the Secretariat of Environment (SEMA) to provide key elements that enable a minimally substantiated diagnosis of the process that led the city to establish such a management mechanism. Also raised were the different approaches to planning, beyond Balanced Scorecard (BSC), the context of the theme in the world and in Brazil and the practical results in other municipalities of the same size in a synthesized form. Due to the relevance and timeliness of the topic, related to New Public Management (NGP), a diagnosis was made based on their critical points and improvement possibilities regarding the deployment and perpetuation of the culture of management for results in the county. It is sought to contribute to the improvement of the formulation and implementation of strategic planning with practical mechanisms and suggestions.